POLITIK HUKUM PENYELENGGARAAN OTONOMI DAERAH DALAM PERSPEKTIF NEGARA KESATUAN REPUBLIK INDONESIA - Sri Kusriyah (UNISSULA, 2016)
The 1945 Constitution is the highest law in Indonesia. From 1999 to 2002 has experienced four stages of change which were conducted democratically, constitutionally and institutionally bythe Assembly. The setting changes include the Article 18 of the regulation of local government. The Article 18 of the State Constitution RI 1945 is currently implemented by Act No. 23 of 2014 on Regional Government, as the basis of political regional autonomy law in Indonesia. The problem in this research are: how do the the central government and local government be divided in term of authority, how do public services is guaranteed, how do the organizers of local government competency is standardized?, and how do the principles of governance in the Islamic view? The results of the research reveals that Politics Regional Autonomy Law byLaw No. 23 of 2014 the local government is still under control by central Government. Public Service guarantee the principles of the public service. The scope of public services includes: services of public goods and public services as well as administrative services. Management of Public Service, Local Government shall establish public service management with reference to the principles of public service. The Governance Principles in the Perspective of Islam, can be traced in the Qur’an and Hadith include: Power as a mandate, the Council, to uphold the rule of law and justice, leadership, responsibility of leaders, relationship between the leader and the led is based on brotherhood and careness.